Metas, controle e neoliberalismo no Tribunal de Justiça do Estado do Ceará: uma análise a partir das noções de dispositivo e de biopoder - Lima, Stéfano Gonçalves (2025)
Targets have become commonplace in contemporary work, a reality that can be observed in both the private and public sectors. But what is the rationale behind these practices? In view of this, it is important to understand how certain techniques adopted by the Tribunal de Justiça do Estado do Ceará (TJCE) work, such as strategic planning and the Gratificação por Alcance de Metas Estratégicas (GAM). It is also necessary to understand the way in which these techniques are present in the mentality of the members of this court. To this end, an analysis inspired by Michel Foucault's studies was made of the content and justifications of the strategic planning norms of the Conselho Nacional de Justiça (National Council of Justice) and the TJCE, the national goals of the Judiciary and the norms that instituted and regulate the GAM, with the aim of understanding them not only as an system, but as technologies of biopower that foster a norm standard. In addition, qualitative semi-structured interviews were carried out with members of the gold seal judicial courts in order to ascertain, through analysis of the recorded statements and the knowledge-power relations presupposed, how the processes of subjectivation, desubjectivation and resistance to the goals and logic of strategic management take place in the work environment of these units. Finally, the data collected was articulated with the bibliographic discussions of the critical paradigm to neoliberalism, focusing on Christian Laval, Pierre Dardot, Wendy Brown and Grégoire Chamayou, with the aim of understanding and verifying what knowledge and strategies guide the management process in these units. The final findings of the study were that the ultimate aim of management and targets is not for them to be achieved, but for a managed, efficient and proactive environment to be produced, with the incorporation of the norm standard. This process functions as a neoliberal judicial dispositif, in which biopower technologies are used to dispose of bodies and populations in the most efficient way, following a technocratic logic. It was also concluded that this dispositif is part of a broader context of neoliberal rationality, which promotes, among other phenomena, the emptying of the political dimension of democratic public life, the austere management of resources according to unequal networks of symbolic capital and a strategic exhaustion of available human resources, based on the logic of competition.